2022
DOI: 10.3389/fphar.2022.901099
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacist-Urologist Collaborative Management Improves Clinical Outcomes in Patients With Castration-Resistant Prostate Cancer Receiving Enzalutamide

Abstract: Background: Enzalutamide is useful for the treatment of castration-resistant prostate cancer (CRPC). Despite its usefulness, adverse events (AEs) sometimes force patients to discontinue treatment. To maximize patient care, we developed an ambulatory care pharmacy practice that allows collaboration between a pharmacist and urologist to manage patients with CRPC receiving enzalutamide. In this study, we investigated the efficacy of this collaborative management.Methods: A retrospective chart review of 103 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 38 publications
(59 reference statements)
1
4
0
Order By: Relevance
“…Numerous studies have shown the effectiveness of pharmacist-led team care in pharmacotherapies. [6][7][8][9][10][13][14][15][16][17][18][19] The results of this study also supported the usefulness of pharmacisturologist collaborative pharmacotherapy management in an ambulatory care setting. In our ambulatory care pharmacy practice, pharmacists performed a variety of responsibilities, including patient education, suggesting appropriate supportive care, suggesting pazopanib dose modifications to physicians if necessary, managing drug-drug interactions, and encouraging patients to take their medication as prescribed.…”
Section: Discussionsupporting
confidence: 72%
See 4 more Smart Citations
“…Numerous studies have shown the effectiveness of pharmacist-led team care in pharmacotherapies. [6][7][8][9][10][13][14][15][16][17][18][19] The results of this study also supported the usefulness of pharmacisturologist collaborative pharmacotherapy management in an ambulatory care setting. In our ambulatory care pharmacy practice, pharmacists performed a variety of responsibilities, including patient education, suggesting appropriate supportive care, suggesting pazopanib dose modifications to physicians if necessary, managing drug-drug interactions, and encouraging patients to take their medication as prescribed.…”
Section: Discussionsupporting
confidence: 72%
“…The objectives of our collaborative management were to support urologists in patient care. [6][7][8] Three board-certified oncology pharmacists in Japan worked in the ambulatory care pharmacy practice. Their average experience as pharmacists was 21.7 and 15.3 years in general practice and oncology, respectively.…”
Section: Implementing Pharmacist-urologist Collaborative Management F...mentioning
confidence: 99%
See 3 more Smart Citations